The spatial spillover effects of tax policy reform on fiscal sustainability: A spatial econometric analysis based on provincial-level data in China - Zhang, Ke; Fu, Kun (Edelweiss Applied Science and Technology, 2025)
This study employs spatial econometric analysis (SAR and SLM models) to examine the spatial spillover effects of tax and fee reduction policies (Policy Effect) and Foreign Direct Investment (FDI) on fiscal sustainability across Chinese provinces. Using provincial-level data, it investigates impacts on GDP per capita and technological progress (measured by Malmquist Technology Progress Index, MTPI), considering Population Growth Rate (PGR), Unemployment Rate (UR), and Consumer Price Index (CPI) as mediating/moderating factors. Results reveal significant positive spatial spillovers: tax reforms enhance both GDP per capita and technological advancement in neighboring regions. However, CPI acts as a key moderator, dampening these positive effects and underscoring inflation’s role in fiscal sustainability. The findings emphasize the critical importance of spatially interconnected tax policies for promoting balanced regional economic performance and technology diffusion. Policymakers must account for these cross-jurisdictional spillovers to design effective fiscal reforms that foster sustainable growth.